Analysis of the Social Transformation of the Principal: A study at Madrasah Aliyah Raudhatul Ulum Meranti - Wakip, Abdul; Rustiyarso, Rustiyarso; Zakso, Amrazi (Universitas Tanjungpura, 2024)
This study uses a qualitative research method with a descriptive approach. This study aims to analyze of social transformation of school head at Madrasah Aliyah Raudhatul Ulum Meranti, where this social transformation focuses on the transformation of ideas and the transformation of actions. The location of this research is at Madrasah Aliyah Raudhatul Ulum Meranti, which is located in Meranti Village, Sungai Ambawang District, Kubu Raya Regency. The data collection techniques in this study are observation, interview, and documentation. While the data collection tools are observation guidelines, interview guidelines, and documentation studies. In data analysis techniques, the writer uses data reduction, data display, and data verification. The result of this study shows that there are positive and negative responses in applying the transformation of ideas and transformation of actions to the school head of MAS Raudhatul Ulum Meranti. The positive responses came from school residents, student guardians, and the surrounding community by assessing the social transformation carried out by the school principal as an achievement that had never been carried out by the previous school head. while the negative response came from some school residents, student guardians and the surrounding community because the social transformation they carried out paid little attention to the social, economic conditions and habits of the people there and the lack of socialization before the transformation was carried out. This is what later gave rise to polemics, which included strained social relations between school head, school residents, the surrounding community and the student guardians.